Chitosan-based dressings loaded with neurotensin—an efficient strategy to improve early diabetic wound healing - Moura, Liane I. F. (2014)
One important complication of diabetes mellitus is chronic, non-healing diabetic foot ulcers (DFUs). This study aims to develop and use dressings based on chitosan derivatives for the sustained delivery of neurotensin (NT), a neuropeptide that acts as an inflammatory modulator in wound healing. Three different derivatives, namely N-carboxymethyl chitosan, 5-methyl pyrrolidinone chitosan (MPC) and N-succinyl chitosan, are presented as potential biomaterials for wound healing applications. Our results show that MPC has the best fluid handling capacity and delivery profile, also being non-toxic to Raw 264.7 and HaCaT cells. NT-loaded and non-loaded MPC dressings were applied to control/diabetic wounds to evaluate their in vitro/in vivo performance. The results show that the former induced more rapid healing (50% wound area reduction) in the early phases of wound healing in diabetic mice. A NT-loaded MPC foam also reduced expression of the inflammatory cytokine TNF-α (P < 0.001) and decreased the amount of inflammatory infiltrate on day 3. On day 10 MMP-9 was reduced in diabetic skin (P < 0.001), significantly increasing fibroblast migration and collagen (COL1A1, COL1A2 and COL3A1) expression and deposition. These results suggest that MPC-based dressings may work as an effective support for sustained NT release to reduce DFUs.